Customer Satisfaction Level on the Quality of Services PT. Garuda Indonesia in Nabire District - Letarius Tunjanan (Budapest International Research and Critics University, 2022)
PT. Garuda Indonesia is one of the airlines that offers quality services by prioritizing the safety and security aspects of flights operating in Nabire City with ticket prices that Garuda Indonesia in Nabire City is different from other cities. The price offered by PT. PT Garuda Indonesia in carrying out its operations does not run alone because the management and administration cooperate with PT Guna Indah Raya in terms of ticketing sales services and other services related to the operations of PT Garuda Indonesia. Research Objectives To find out how the efforts made by PT. Garuda Indonesia in improving the quality of services so that the level of customer satisfaction increases in Nabire Regency. To find out what factors affect PT. Garuda Indonesia in improving the quality of services so that the level of customer satisfaction increases in Nabire Regency. The method used in this research is descriptive. The results showed that PT. Garuda Indonesia always maintains the best flight quality for customers and the public. PT. Garuda Indonesia always provides convenience in ticketing services. Besides that, PT. Garuda Indonesia always pays more attention to customers and the public. Garuda Indonesia always provides convenience in ticketing services. Besides that, PT. Garuda Indonesia always pays more attention to customers and the public. Garuda Indonesia always provides convenience in ticketing services. Besides that, PT. Garuda Indonesia always pays more attention to customers and the public.